Capacity constrained price competition with transportation costs - Johannes Muthers; Matthias Hunold (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We characterize mixed-strategy equilibria in case of capacity constrained price competition, transportation costs and customer-specific pricing. Equilibrium prices weakly increase in the distance between supplier and customer. Despite prices above costs and excess capacities, the firms exclusively their serve home markets. Competition yields volatile market shares and an inefficient allocation of more distant customers to suppliers. Even ex-post subcontracts may restore efficiency only partly.
Keywords: L11; 330